Career decision making self efficacy and lifestyle: measuring the characteristics of millennial workers - Rina Indra Sabella (Institute of Computer Science (IOCS), 2024)
The aim of the research is to identify this lifestyle as well as measure self-confidence in career decisions (CDMSE), which in measuring lifestyle uses the value, attitude and lifestyle segment (VALS-2). Sampling was taken non-probability, on 124 job applicants who had or were currently working, and data was collected using the CDMSE scale and lifestyle taken from the VALS-2 concept, which was then carried out by K-Mean cluster analysis. It can be concluded that the lifestyle of millennial employees and CDMSE can be divided into 5 types of lifestyle, namely: 1) millennial holic lifestyle who have very high career confidence; 2) the sabotaging lifestyle has high career beliefs, and this lifestyle believes in the position that is being held, but its attitude tends to avoid competition and work conflict in achieving its career; 3) the millennial lifestyle has relatively high confidence and the characteristics of employees who like to attract the attention of many people; 4) millennial conformity lifestyle with the characteristic of easily following social trends or influences to make changes in attitudes and behavior to match the character of social norms; and 5) the aut-millennial lifestyle which has autistic behavior and ways of thinking, namely thinking and carrying out activities that are more self-oriented. These millennial employees show more personal thinking, liking symbols with personally translated meanings. Employees with an autistic lifestyle will show work behavior that is more focused and in-depth with one area of work where the activity is as if it were a dialogue